Feasibility of hydroxypropyl methylcellulose oleogel as an animal fat replacer for meat patties. (August 2019) - Oh, Imkyung; Lee, JaeHwan; Lee, Hyeon Gyu; Lee, Suyong
Abstract: Canola oil was successfully structured with foam-structured hydroxypropyl methylcellulose (HPMC) into solid-like oleogels, and the feasibility of the HPMC oleogels as a replacement for animal fat (beef tallow) was evaluated to reduce the level of saturated fat in meat patties. The textural properties (firmness and work of shear) of HPMC oleogels were higher than those of beef tallow and had a tendency to increase with increasing levels of HPMC in the oleogels. HPMC oleogels behaved rheologically like an elastic gel and also exhibited temperature-independent solid fat contents. They exhibited greater resistance against oxidation than the canola oil under the accelerated storage condition. When the beef tallow in the formulation of meat patties was replaced with HPMC oleogels at 50% and 100%, the cooking loss of the patties was significantly reduced, and their texture became much softer. Furthermore, the sensory evaluation indicated that the highest overall acceptability was attained at the 50% replacement level. The replacement of beef tallow with HPMC oleogels was significantly effective in reducing the ratio of saturated to unsaturated fat from 0.73 to 0.18, consequently producing meat patties with nutritional superiority. Graphical abstract: Unlabelled Image Highlights: HPMC oleogel was used as an animal fat replacer for saturated fat-reduced meat patty. Oleogel with a firmer texture had more gel-like behavior and oxidative stability. Use of oleogel for animal fat produced patties with lower cooking loss/softer texture. The highest sensory acceptability was obtained at the 50% replacement level. Animal fat replacement with HPMC oleogel reduced saturated fat level from 42% to 15%.